Combination of Direct Antiviral Therapy in Hepatitis C Patients, Population of Karachi - Samia Perwaiz Khan; Muslim Abbas; Ajeet Kumar; Fadieleh A. Sohail; Rubina Ghani (ziauddin University, 2020)
Background: Pakistan has approximately eight million Hepatitis C Virus (HCV) infected patients. Initial regimen of interferon-based along with ribavirin showed SVR (Sustained Virological Response Rate) of up to 50%. The new standard Direct Acting Antiviral (DAA) therapy with improved response rates raised SVR rates to as high as 90%. This study was conducted to determine the outcome of the novel combined DAA regimen in hepatitis C infected patients in Karachi, Pakistan. Methods: Fifty patients with infected with HCV were participants of this study. They were from the gastroenterology ward and OPD Jinnah Medical Hospital (JMCH), Karachi. Initial investigations included blood samples for complete picture (CP) and liver function test (LFT). After performing qualitative Polymerase Chain Reaction (PCR), patients diagnosed with hepatitis C (pangenotypes) were prescribed DAA therapy. Results: Out of total fifty patients diagnosed with HCV infection, forty compensated patients of hepatitis C were prescribed combination of Sofosbuvir and Velpatasvir, of these thirty five patients (100%) had shown to be PCR negative after three months of therapy and negative PCR after 3 months follow-up, five patients were lost to follow up. Ten patients decompensated (with ascites, cirrhosis or hepatic encephalopathy) were prescribed Sofosbuvir + Velpatasvir along with ribavirin, seven (100%) had shown to be PCR negative and three were lost to follow up. Conclusion: Sofosbuvir and Velpatasvir was most effective combination of direct antiviral regimen in treatment of HCV pan-genotype patients, with least adverse-effects and much better outcome in both compensated and decompensated (with ascites and cirrhosis) hepatitis C infected patients. Keywords: DAA-Direct-Acting Antiviral Agents; NS Protein; Polymerase Inhibitor; Protease Inhibitor; ETR-End Treatment Response, SVR-Sustained Virological Response.